The context of science fiction in the pre-service teachers’ chemistry education - Vošnjak Matej; Devetak Iztok (Chemistry Teacher International, 2023)
Context-based teaching and learning has a long tradition in science, especially chemistry. Audiovisual media (movies and series) can be used to provide context, and it can help overcome many students’ negative attitudes toward real science. An example of audiovisual media in which a science context can be presented is science fiction (abbreviated Sci-Fi). The purpose of this study was to investigate how the Sci-Fi context influences pre-service teachers’ attitudes and perceptions regarding the use of Sci-Fi for teaching and learning science, with a focus on chemistry, as a result of a 15-week novel elective Sci-Fi course for pre-service teachers. The main instruments used were online questionnaires, a final exam, and a rubric-based presentation evaluation form. The results of our study show that the majority of pre-service teachers consider the Sci-Fi context to be a very interesting context for science education, especially chemistry, and a useful tool for promoting students’ interest in science. Students believe that it is important to incorporate the Sci-Fi context into chemistry instruction at all levels. Our results suggest that the Sci-Fi context is useful to students as an alternative learning method that can be used to improve student learning outcomes.